“To us the war is a spectacle”: Domestic Consumption of the Crimean War in Victorian Britain - Alison Fletcher (Cahiers Victoriens et Edouardiens)
During the Crimean War, civilian war correspondents, most notably William Russell, kept the British public informed about the mismanagement of the war. The administrative shortcomings and the suffering of wounded soldiers shocked the British public and raised concerns about the effectiveness of the army. Following the war, Mary Seacole a colonial subject from Jamaica, published a memoir of her experiences nursing sick soldiers in the Crimea. Her book, which valorized the soldiers and their military leader Lord Raglan, became an immediate best seller. Not only did her book reinforce confidence in the individual soldier and the army more generally, but she demonstrated forcefully that a woman could find a place for herself in the masculine preserve of war.